Carotenoids in orange carrots mitigate non-alcoholic fatty liver disease progression - Balbuena, Emilio; Cheng, Junrui; Eroglu, Abdulkerim (Frontiers in Nutrition, 2022)
(1) Background: Carotenoids are abundant in colored fruits and vegetables. Non-alcoholic fatty liver disease (NAFLD) is a global burden and risk factor for end-stage hepatic diseases. This study aims to compare the anti-NAFLD efficacy between carotenoid-rich and carotenoid-deficient vegetables. (2) Methods: Male C57BL/6J mice were randomized to one of four experimental diets for 15 weeks (n=12 animals/group): Low-fat diet (LFD, 10% calories from fat), high-fat diet (HFD, 60% calories from fat), HFD with 20% white carrot powders (HFD+WC), or with 20% orange carrot powders (HFD+OC). (3) Results: We observed that carotenoids in the orange carrots reduced HFD-induced weight gain, better than white carrots. Histological and triglyceride (TG) analyses revealed significantly decreased HFD-induced hepatic lipid deposition and TG increase in the HFD+WC group, which was further reduced in the HFD+OC group. Western blot analysis demonstrated inconsistent changes of fatty acid synthesis-related proteins but significantly improved ACOX-1 and CPT-II, indicating that orange carrot carotenoids had the potential to inhibit NAFLD by improving β-oxidation. Further mechanistic investigation showed significantly higher mRNA and protein levels of PPARα and its transcription factor activity. (4) Conclusions: Carotenoid-rich foods may display more potent efficacy in mitigating NAFLD than those with low carotenoid levels.